2015
DOI: 10.1002/jez.1894
|View full text |Cite
|
Sign up to set email alerts
|

House finch responses to Mycoplasma gallisepticum infection do not vary with experimentally increased aggression

Abstract: Aggression can alter infectious disease dynamics through two, non-exclusive mechanisms: 1) increasing direct contact among hosts and 2) altering hosts' physiological response to pathogens. Here we examined the latter mechanism in a social songbird by manipulating intraspecific aggression in the absence of direct physical contact. We asked whether the extent of aggression an individual experiences alters glucocorticoid levels, androgen levels, and individual responses to infection in an ecologically relevant di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…Intriguingly, we found that pre-infection CORT concentrations interacted with sex in our study: male house finches with higher pre-infection CORT concentrations showed lower overall disease severity and pathogen load in response to MG infection, whereas female pre-infection CORT concentrations did not significantly predict individual variation in either metric. Our results are consistent with those of Adelman et al (2015), who found that higher pre-infection baseline CORT concentrations were predictive of lower disease severity among male house finches. It is intriguing that we did not detect a significant relationship between pre-infection CORT and disease response within female house finches, despite having a larger sample size for this group.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Intriguingly, we found that pre-infection CORT concentrations interacted with sex in our study: male house finches with higher pre-infection CORT concentrations showed lower overall disease severity and pathogen load in response to MG infection, whereas female pre-infection CORT concentrations did not significantly predict individual variation in either metric. Our results are consistent with those of Adelman et al (2015), who found that higher pre-infection baseline CORT concentrations were predictive of lower disease severity among male house finches. It is intriguing that we did not detect a significant relationship between pre-infection CORT and disease response within female house finches, despite having a larger sample size for this group.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, we examined whether CORT concentrations prior to infection were predictive of individual variation in disease outcome, as has been detected in prior work on male house finches (Adelman et al, 2015). Intriguingly, we found that pre-infection CORT concentrations interacted with sex in our study: male house finches with higher pre-infection CORT concentrations showed lower overall disease severity and pathogen load in response to MG infection, whereas female pre-infection CORT concentrations did not significantly predict individual variation in either metric.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…From these videos we observed 175 instances in which one house finch arrived at a feeding port within 2s of another departing. On all 175 occasions, the arriving finch exhibited aggression, defined as "a rapid movement…made directly at the other bird" (Adelman et al, 2015a).…”
Section: Extracting Behavioral Metrics Using Radiofrequency Identificmentioning
confidence: 99%